Digital mapping of relevant food insecurity information among post flood victim at Bera district, Pahang, Malaysia / Siti Salwani Musa - Musa, Siti Salwani (2016)
Flood is one of the natural phenomenon that have high potential to cause damage in terms of loss of lives, destruction to property and economic loss. This cross sectional study conducted by using convenience sampling method. The objective of this study is to demonstrate and illustrate the factors affecting food insecurity among the flood victims at Bera, Malaysia on the digital mapping by using the Geographic Information System (GIS) as the study on the factors of food insecurity and the illustration of the factors through the digital mapping is limited. The combination of questionnaire from the Household Food Security Survey Model (HFSSM), Household Food Insecurity Access Field (HFIAS), and anthropometric assessment with some modification were used in this study. There were 210 of respondents out of 247 respondents were agree .to be interviewed. Chi square and logistic regression were utilized to know the factors that associated with household food insecurity. The results show that the percentage of the household with food insecure was 29.6% (n=73) according to HFSSM. Thirteen out of seventeen villages have been identified as food insecure in which the three highest food insecure were Kampung Padang Luas (50%), Kampung Kuala Triang (53.8%), and Kampung Bohor Bharu (53.3%). This paper highlight on the factors of food insecurity and on how the GIS application help to demonstrate and visualize the area of food insecurity at Bera, Malaysia.